Prescribing and evaluating target dose in dose-painting treatment plans. (September 2014) - Håkansson, Katrin; Specht, Lena; Aznar, Marianne C.; Rasmussen, Jacob H.; Bentzen, Søren M.; Vogelius, Ivan R.
Abstract: Background. Assessment of target dose conformity in multi-dose-level treatment plans is challenging due to inevitable over/underdosage at the border zone between dose levels. Here, we evaluate different target dose prescription planning aims and approaches to evaluate the relative merit of such plans. A quality volume histogram (QVH) tool for history-based evaluation is proposed. Material and methods. Twenty head and neck cancer dose-painting plans with five prescription levels were evaluated, as well as clinically delivered simultaneous integrated boost (SIB) plans from 2010 and 2012. The QVH tool was used for target dose comparison between groups of plans, and to identify and improve a suboptimal dose-painting plan. Results. Comparison of 2010 and 2012 treatment plans with the QVH tool demonstrated that 2012 plans have decreased underdosed volume at the expense of increased overdosed volume relative to the 2010 plans. This shift had not been detected previously. One suboptimal dose-painting plan was compared to the 'normal zone' of the QVH tool and could be improved by re-optimization. Conclusion. The QVH tool provides a method to assess target dose conformity in dose-painting and multi-dose-level plans. The tool can be useful for quality assurance of multi-center trials, and for visualizing the development of treatment planning in routine clinical practice.